Resisting Islamophobia: A Young Muslim Male's Experience in a U.S. Public High School. Issue 3 (3rd July 2019) - Wheatley, Lance
Abstract: What happens when public school students are marginalized because of their religious beliefs, and what means of resistance do some of these students enact against their oppression? This work extends the conversation of Muslim students' experiences in schools to focus on how one male Muslim student experiences religious discrimination and resists that discrimination. During a phenomenological interview, the student recounted his encounters with and his resistance to Islamophobia. This work suggests that some students who are faced with religious discrimination have options to creatively and effectively use a variety of methods of resistance to combat injustice.